Empowering Mothers Through Megamor Innovation (Mega Programme with Moringa Nuggets) to Prevent and Help Overcome Stunting: Pemberdayaan Ibu Melalui Inovasi Megamor (Mega Program dengan Nugget Kelor) untuk Mencegah dan membantu mengatasi Stunting - kundarti, Finta isti; Titisari, Ira; Rahayu, Dwi Estuning; putri, Alvi Nur Puspita; Khammidah, Rysma Dhella (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2025)
Stunting is a severe form of malnutrition and causes a person's weight to drop significantly quickly. In Keniten Village, RT/RW 001/004, cases of stunting among toddlers were found. This community service aims to increase the knowledge of mothers of toddlers about toddler nutrition and innovations in how to process food sourced from local wisdom, namely moringa leaves, which have high nutritional value. This community service activity was carried out in 1 meeting. This activity begins with counseling about toddler nutrition to mothers of toddlers, lasting 30 minutes. Then, the activity will continue with a Moringa Nugget cooking demonstration, which will last 30 minutes. This activity was attended by 17 mothers of toddlers and their toddlers. The cooking demonstration activity starts with preparing the tools and ingredients needed and then practicing how to process moringa leaves into Moringa nuggets. The results of the interviews and post-tests showed an increase in the understanding and skills of mothers of toddlers regarding understanding of children's nutrition, as well as innovations in processing additional food from local moringa leaves into Moringa nuggets. Suggestions for further community service activities include developing additional food processing innovations that are more diverse based on local ingredients often found in the surrounding area.